Intellectual property at the edge : the contested contours of IP - Dreyfuss, Rochelle Cooper, 1947-; Ginsburg, Jane C. (Cambridge intellectual property and information law., 2014)
Intellectual Property at the Edge exposes and analyses newly emerging intellectual property rights and limitations from historical and comparative law perspectives.